Nucleotide sequences of the tolA and tolB genes and localization of their products, components of a multistep translocation system in Escherichia coli. - Levengood, S K (1989)
Various mutations in the tolQRAB gene cluster of Escherichia coli render the bacteria tolerant to high concentrations of the E, A, or K colicins as well as tolerant to infection by the single-stranded filamentous bacteriophage. The nucleotide sequence of a 2.8-kilobase fragment containing the tolA and tolB genes was determined. This sequence predicts TolA to be a 421-amino-acid protein of molecular mass 44,190 daltons. Studies using minicells show it to be associated with the inner membrane, presumably via a 21-amino-acid hydrophobic sequence between residues 13 and 35. The remaining 387 residues on the carboxyl side of this region are located in the periplasm. Within this region of TolA is a 230-residue portion that is predicted to form a very long helical segment. This region is rich in alanine, lysine, and glutamic and aspartic acids. The TolB protein is predicted to contain 431 amino acids. Localization studies using minicells show two proteins encoded by this open reading frame. The larger protein of 47.5 kilodaltons appears to be associated with the membrane fractions. The smaller protein is 43 kilodaltons in size and is found with the periplasmic components of the cell.